2008
DOI: 10.1167/iovs.07-1564
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Curvature and Axial Length Values in Children with Congenital/Infantile Cataract in the First 42 Months of Life

Abstract: In the first 42 months of age, K(m) and AL are significantly different according to age. These findings have implications for the calculation of intraocular lens power in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
50
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(69 citation statements)
references
References 30 publications
8
50
3
6
Order By: Relevance
“…These conditions probably influenced these values and their relationships with age and AL, generating a poor correlation (R 2 =0.11). These findings have already been described by other authors, who also found weaker relationships between K and age, with R 2 varying from 0.31 (17) to 0.20 (7) , as well as between K and AL (R 2 =0.32) (17) , despite the larger sample sizes. Due to the difficulty of obtaining these values, the measurement method used in the present study still seems to be the best manner to obtain K values; however, a device that allows more accurate measurements may establish prediction models with more precise estimates of K in relation to age and AL.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These conditions probably influenced these values and their relationships with age and AL, generating a poor correlation (R 2 =0.11). These findings have already been described by other authors, who also found weaker relationships between K and age, with R 2 varying from 0.31 (17) to 0.20 (7) , as well as between K and AL (R 2 =0.32) (17) , despite the larger sample sizes. Due to the difficulty of obtaining these values, the measurement method used in the present study still seems to be the best manner to obtain K values; however, a device that allows more accurate measurements may establish prediction models with more precise estimates of K in relation to age and AL.…”
Section: Discussionsupporting
confidence: 88%
“…Two papers have described K and AL measurements in North American children with congenital cataract (5,17) . Further, a study in Italy showed the AL and K values of a Caucasian pediatric population with congenital/developmental cataract (7) . Databanks containing biometric information from eyes with pediatric cataract allow estimation of the ocular values of AL and K based on age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most striking aspect of our study was that it was not performed with postmortem subjects or with congenital cataract patients, as could be observed in some studies (2,3) .…”
Section: Discussionmentioning
confidence: 99%
“…Le pic de croissance oculaire a lieu la première année et la longueur axiale évolue rapidement, ce n'est qu'après trois ans que l'oeil atteint sa longueur quasiment définitive [14]. La kératométrie, quant à elle, se modifie très rapidement avec une stabilisation semblant plus précoce [15,16]. Le problème de la prédictibilité de la puissance de l'implant, selon l'âge de l'enfant, reste donc présent dans la prise en charge des cataractes congénitales.…”
Section: Discussionunclassified